Preoperative serum hyaluronic acid level as a prognostic factor in patients undergoing hepatic resection for hepatocellular carcinoma. Issue 3 (20th January 2014) - Mima, K.; Beppu, T.; Ishiko, T.; Chikamoto, A.; Nakagawa, S.; Hayashi, H.; Watanabe, M.; Sakamaki, K.; Baba, H.
<x xml:space="preserve">Abstract</x> Background Hyaluronic acid (HA) probably plays a critical role in tumorigenesis. The clinical significance of serum HA concentration in patients with hepatocellular carcinoma (HCC) remains to be elucidated. This study analysed the relationship between preoperative serum HA levels and prognosis after hepatic resection in patients with HCC. Methods Consecutive patients who underwent hepatic resection for HCC between September 1999 and March 2012 were included in this retrospective study. Serum HA levels were measured within 4 weeks before surgery by an immunoturbidimetric automated latex assay. The cut‐off level for preoperative serum HA was validated using a time‐dependent receiver operating characteristic (ROC) curve analysis. The prognostic impact of preoperative serum HA levels was analysed using Cox proportional hazards models. Results A total of 506 patients of median age 66 years (405 men, 80·0 per cent) were analysed. The median length of follow‐up was 32 months. High serum HA levels (100 ng/ml or above) were associated with shorter recurrence‐free survival (P < 0·001) (hazard ratio (HR) 1·50, 95 per cent confidence interval 1·17 to 1·93; P = 0·002) and overall survival (P = 0·001) (HR 1·46, 1·03 to 2·07; P = 0·033). In patients with HCC without severe liver fibrosis, serum HA level was correlated with multiple tumours (P = 0·039), early recurrence (P = 0·033), and poor recurrence‐free (P < 0·001) and overall (P = 0·024) survival. Conclusion High preoperative serum HA levels predict poor prognosis in patients with HCC after hepatic resection, and may serve as a future biomarker.